2020
DOI: 10.3390/jcm9072103
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Lowering—From Lipoprotein Apheresis to Antisense Oligonucleotide Approach

Abstract: It is well-known that elevated lipoprotein(a)—Lp(a)—levels are associated with a higher risk of cardiovascular (CV) mortality and all-cause mortality, although a standard pharmacotherapeutic approach is still undefined for patients with high CV risk dependent on hyperlipoproteinemia(a). Combined with high Lp(a) levels, familial hypercholesterolemia (FH) leads to a greater CVD risk. In suspected FH patients, the proportion of cases explained by a rise of Lp(a) levels ranges between 5% and 20%. In the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 162 publications
(190 reference statements)
1
23
0
Order By: Relevance
“…Despite the similarity of the structural organization of Lp(a) and LDL particles and the presence of an apoB100 molecule in both, the LDL receptor was shown not to be important for the catabolism of Lp(a), in transgenic animals [ 19 ], cell models [ 20 ], clinically [ 7 , 21 ] and in kinetic studies [ 22 ]. Statins promote the increase in the number of LDL receptors on hepatocytes and result in an increase of Lp(a) concentration versus a decline of LDL-C [ 2 ]. However, it has been shown that Lp(a) internalization by hepatocyte cell lines increased both after the enhanced expression of LDL receptor and blocking of PCSK9 synthesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the similarity of the structural organization of Lp(a) and LDL particles and the presence of an apoB100 molecule in both, the LDL receptor was shown not to be important for the catabolism of Lp(a), in transgenic animals [ 19 ], cell models [ 20 ], clinically [ 7 , 21 ] and in kinetic studies [ 22 ]. Statins promote the increase in the number of LDL receptors on hepatocytes and result in an increase of Lp(a) concentration versus a decline of LDL-C [ 2 ]. However, it has been shown that Lp(a) internalization by hepatocyte cell lines increased both after the enhanced expression of LDL receptor and blocking of PCSK9 synthesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Lp(a) particle consists of an apoB100-containing low-density lipoprotein (LDL)-like particle covalently linked to a highly glycosylated and extremely polymorphic apolipoprotein(a) [apo(a)]. Plasma levels of Lp(a) are genetically controlled and cannot be reduced by statins, while the application of high doses of nicotinic acid has only minor effects on its concentration [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the association between Lp(a) elevations and coronary artery disease risk has emerged from both epidemiological and genetic studies [64][65][66], a pharmacological approach able to lower Lp(a) levels to the extent required to potentially achieve a CV benefit in patients with progressive ASCVD and high plasma Lp(a) is still missing (reviewed in [67]). Available lipid-lowering therapies have little value for Lp(a) reduction.…”
Section: Lp(a)-novelties In the Era Of Rna-based Therapiesmentioning
confidence: 99%
“…Lp(a) levels are associated with a high risk of cardiovascular mortality, requiring a new pharmacotherapeutic approach, and 5–20% of patients suspected of FH had elevated Lp(a) levels [ 51 ]. In our study, we did not measure the Lp(a) values, but these findings will be exploited in a future study in which the Lp(a) of the patients will be assessed.…”
Section: Discussionmentioning
confidence: 99%